DETERMINING THE INFLUENCE OF POWER POINT SLIDE TOWARD STUDENTS MOTIVATION IN LEARNING ENGLISH - Enni Akhmad Daud; noning t rivai (Al-Lisan: Jurnal Bahasa, 2018)
This study aims to determine the influence of the using power point slides on the motivation of students in learning English. The study formulated into research question â€œis there influence of using power point toward studentsâ€™ motivation?â€ This study used quantitative research by taking sample 37 students at MTs Negeri Model Limboto through random sampling technique. The instrument of this study was questionnaire. The data analyzed through the formula Pearson product moment and Correlation product moment. The result of this study shown that there is strong influence of using power point slide toward studentsâ€™ motivation in learning English. The significant influence can be seen in the result of data analyzed.